Strategi Kepemimpinan Dalam Partai Golongan Karya Di Kota Padang - Difki Aulia Rahman; Elsa Nanda Muharnisa; Fadillah Gusti Ardira; Fazwa Maura Zacky; Muhammad Zaki (CV. ITTC INDONESIA, 2024)
Leadership is the ability of a leader to control, lead, and influence the thoughts, feelings, or behavior of others to achieve predetermined goals. In the context of public leadership, officials from political parties or from professional backgrounds often cannot separate personal (party) interests from the broader public interest. The method used in this research is qualitative research. The strategy employed by political parties in the process of regeneration and filling national leadership roles includes recruitment, education, and development of political cadres.